Penerapan Metode Proper Matching Pada Perusahaan Kontraktor - Jeanne Asteria Wawolangi; Deograsias Yoseph Yustinianus Ferdinand (Universitas Katolik Darma Cendika, 2020)
The purpose of this study is to evaluate the methods used in the recognition of construction contract revenue and to apply the proper matching method tocontractor companies. The object of research is the construction project of smallscale houses and shophouses carried out by the Baron Residence constructioncompany located in Magetan, East Java. This research is classified as qualitative research. From the results of the study, it is known that the company recognizesrevenue using the percentage method of physical progress completion, so that it is not in accordance with the matching principle, namely the income that occurs in a period is compared with the costs incurred to earn income in the same period. The solution given is for the company to use the cost to cost percentagecompletion method, so that the income received is in accordance with the physical building. This is useful in presenting accurate information in making decisionsand fulfilling the principle of reliability, which is one of the characteristics of financial statements.